2006
DOI: 10.1086/498339
|View full text |Cite
|
Sign up to set email alerts
|

Speckle Statistics in Adaptively Corrected Images

Abstract: (abridged) Imaging observations are generally affected by a fluctuating background of speckles, a particular problem when detecting faint stellar companions at small angular separations. Knowing the distribution of the speckle intensities at a given location in the image plane is important for understanding the noise limits of companion detection. The speckle noise limit in a long-exposure image is characterized by the intensity variance and the speckle lifetime. In this paper we address the former quantity th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 37 publications
1
83
1
Order By: Relevance
“…Following the work of Goodman (1968), Soummer & Aime (2004), and Fitzgerald & Graham (2006), the speckle intensity PDF for one location in the image plane and random temporal phase errors can be shown to be a modified Rician function. At a specific location in the image plane, the MR PDF p MR (I ) is a function of the local time-averaged static point-spread function (PSF) intensity I c and random speckle noise intensities I s :…”
Section: Speckle Noise Statisticsmentioning
confidence: 94%
See 1 more Smart Citation
“…Following the work of Goodman (1968), Soummer & Aime (2004), and Fitzgerald & Graham (2006), the speckle intensity PDF for one location in the image plane and random temporal phase errors can be shown to be a modified Rician function. At a specific location in the image plane, the MR PDF p MR (I ) is a function of the local time-averaged static point-spread function (PSF) intensity I c and random speckle noise intensities I s :…”
Section: Speckle Noise Statisticsmentioning
confidence: 94%
“…The atmosphere ( Roddier 1981;Racine et al 1999;Macintosh et al 2005), telescopes, and instruments optics ( Marois et al 2003Hinkley et al 2007) produce speckles with a range of timescales that limit the direct detection of faint companions. From previous theoretical analyses, it is known that the speckle intensity temporal distribution is a modified Rician ( MR;Goodman 1968;Soummer & Aime 2004;Fitzgerald & Graham 2006). If a large number of uncorrelated speckle realizations are co-added, we know from the central limit theorem that the final residual speckle noise will follow a Gaussian intensity distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical descriptions of stellar speckles have been proposed by many authors (Racine et al 1999;Fitzgerald & Graham 2006), who showed that speckle noise is not negligible. The distribution of speckle statistics in AO were also studied by Canales & Cagigal (1999).…”
Section: Analysis Methodsmentioning
confidence: 99%
“…It is known that speckle noise does not follow Gaussian statistics (Goodman 1968;Fitzgerald & Graham 2006). However, Marois et al (2008a) have performed a detailed analysis of NIRI data processed with ADI (Marois et al 2006) and demonstrated that the residual noise follows quasi-Gaussian statistics when a sufficient number of images (i.e.…”
Section: Detection Limitsmentioning
confidence: 99%